Differences in the response mechanism of cadmium uptake, transfer, and accumulation of different rice varieties after foliar silicon spraying under cadmium-stressed soil - Zhao, Junyang; Yu, Baoshan; Wang, Xueli; Chen, Lihong; Akhtar, Kashif; Tang, Shide; Lu, Huaming; He, Jinhua; Wen, Ronghui; He, Bing (Frontiers in Plant Science, 2023)
Most studies have shown that foliar silicon (Si) spraying can reduce the risk of rice quality safety caused by Cadmium (Cd) contamination. However, it has recently been found that different rice varieties have different responses to Si. Therefore, we selected six rice varieties (YHSM, YXY1179, YXYLS, JLK1377, MXZ2 and YLY900) to compare the differences in the effects of leaf spray on Cd accumulation among different varieties. According to the change of Cd content in brown rice after Si application, six rice varieties were divided into two types: silicon-inhibited varieties (JLY1377, MXZ2, LY900 and YXYLS) and silicon-stimulated varieties (WY1179 and YHSM). For silicon-inhibited varieties, the Cd content of rice was reduced by 13.5%-65.7% after Si application. At the same time, the Cd content of root, stem, leaf, panicle and glume decreased to different degrees, and the Cd content of cell wall component increased by 2.2%-37.6%, and the extraction state of Cd with strong mobile activity (ethanol-extracted and deionized water-extracted) was changed to the extraction state of Cd with weak mobile activity (acetic acid-extracted and hydrochloric acid-extracted), and the upward transport coefficient of different parts was reduced. For silicon-stimulated varieties, Si application increased the Cd content of rice by 15.7%-24.1%. At the same time, the cell soluble component Cd content significantly increased by 68.4%-252.4%, and changed the weakly mobile extraction state Cd to the strong mobile extraction state, increasing the upward transport coefficient of different sites. In conclusion, different rice varieties have different responses to Si. Foliar Si spraying inhibits the upward migration of Cd of silicon-inhibited varieties, thereby reducing the Cd content of rice, but it has the opposite effect on silicon-stimulated varieties. This result reminds us that we need to consider the difference effect of varieties in the implementation of foliar Si spraying in remediation of Cd-contaminated paddy fields.